2021
DOI: 10.7759/cureus.13078
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of COVID-19: Red Cell Distribution Width, Platelet Distribution Width, and C-Reactive Protein

Abstract: Bommenahalli Gowda et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 11 publications
2
21
3
Order By: Relevance
“…In contrast to what observed in adults [1][2][3], our results do not suggest the existence of clinically significant differences in RDW values in children (0-16 years) according to illness categories, hospitalization, and presence of MIS-C, days of hospitalization or viral load (CT values).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to what observed in adults [1][2][3], our results do not suggest the existence of clinically significant differences in RDW values in children (0-16 years) according to illness categories, hospitalization, and presence of MIS-C, days of hospitalization or viral load (CT values).…”
Section: Discussioncontrasting
confidence: 99%
“…As recently discussed by Bommenahalli Gowda et al [ 1 ], there seems to be an association between red blood cell distribution width (RDW) and adverse outcomes among patients with COVID‐19. Consistent with this, Henry et al [ 2 ] suggested the utility of measuring RDW as a single point prognostic factor for adults admitted in the emergency departments (ED).…”
Section: Introductionmentioning
confidence: 98%
“…RDW conveys the degree of anisocytosis, which is a hugely inflammation-dependent process. Cytokine release and inflammation lead to higher platelet production, and increased PDW and RDW are associated with increased mortality in adults [ 28 ]. In our study, inpatients had statistically higher RDW while there was no significant difference of PDW levels between inpatients and outpatients.…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies reported using MPV in COVID-19 patients who survived and died [19, 24, 25, 37, 38, 40-42]. All studies measured survival and death, except Barrett et al [25] who measured hospitalised patients who had a thrombotic event and death.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported using PDW in COVID-19 patients who survived and died [19, 24, 38, 40, 41]. The pooled mean difference of the PDW values was significantly higher in the non-survivors (SMD = 0.45 [95% CI: 0.19, 0.71], p = 0.0007, n = 948); however, there was substantial heterogeneity by the random effect model ( I 2 = 68%) (Supplementary material 5: Figure 2).…”
Section: Resultsmentioning
confidence: 99%